2022
DOI: 10.1002/jpen.2449
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sarcopenia in patients with chronic intestinal failure—how are SARC‐F and the EWGSOP algorithm associated before and after a physical exercise intervention

Abstract: Introduction Patients with chronic intestinal failure (IF) have a low degree of physical activity, decreased muscle mass, and decreased muscle strength, leading to a high risk of sarcopenia. We aimed to test the prevalence of sarcopenia by the use of SARC‐F and EWGSOP and to investigate the association between the two at baseline and after 12 weeks of an exercise intervention. Methods Thirty‐one patients with chronic IF completed 12 weeks of three weekly home‐based individualized exercise sessions. Body compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
(66 reference statements)
1
4
0
Order By: Relevance
“…The disadvantageous body composition of our cohort is in line with outcomes reported by Køhler et al, who also found a normal mean BMI (20.0 kg/m 2 ), low FFMI (14.8 kg/m 2 ), and 64% FFMI below reference 9 . Two other studies evaluated the prevalence of sarcopenia in patients with CIF 20,21 . Sarcopenia is a progressive skeletal muscle disorder associated with impaired clinical outcomes, for example, lower quality of life and higher morbidity and mortality 3 .…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The disadvantageous body composition of our cohort is in line with outcomes reported by Køhler et al, who also found a normal mean BMI (20.0 kg/m 2 ), low FFMI (14.8 kg/m 2 ), and 64% FFMI below reference 9 . Two other studies evaluated the prevalence of sarcopenia in patients with CIF 20,21 . Sarcopenia is a progressive skeletal muscle disorder associated with impaired clinical outcomes, for example, lower quality of life and higher morbidity and mortality 3 .…”
Section: Discussionsupporting
confidence: 88%
“…For example, the persistent inflammatory state in patients with inflammatory bowel diseases can contribute to metabolic alterations and disruptions in nutrient absorption, ultimately affecting body composition 30 . In addition, we suppose that in line with previous reports in the CIF setting, most patients receiving treatment at our center have a suboptimal body composition because of insufficient exercise 20,31 . However, we could not demonstrate this assumption because our center has only recently implemented accelerometry measurements.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations